Pendekatan Behavioral dalam Menangani Perilaku Bernyanyi pada Mahasiswa Minangkabau: Perspektif Konseling Lintas Budaya - Syajaro Tuddur; Fadhilla Yusri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This article discusses the behavioral approach in handling singing behavior among Minangkabau students from a cross-cultural counseling perspective. Singing behavior is viewed as a form of self-expression, emotional release, entertainment, and habitual activity influenced by personal interests and cultural background. In Minangkabau culture, singing and artistic expression through music are generally considered normal and socially accepted behaviors. However, excessive singing without considering time, place, and social conditions may disturb the surrounding environment. This study aims to analyze the causes, impacts, and counseling interventions related to singing behavior through a qualitative case analysis focusing on a student who frequently sings in a boarding house environment. The findings indicate that singing provides positive effects such as stress reduction, emotional expression, increased self-confidence, and opportunities for talent development. Nevertheless, negative impacts include noise disturbance, discomfort for others, vocal strain, and physical fatigue. The counseling intervention combines behavioral counseling and cross-cultural counseling approaches. Behavioral counseling helps the client develop self-control and adaptive behavior patterns, while cross-cultural counseling emphasizes understanding the client’s cultural background and social values. The interventions include rapport building, psychoeducation, self-control training, and directing the client’s interests and talents into positive activities. The study concludes that counseling interventions considering cultural values and behavioral aspects can help clients express themselves positively without disturbing their social environment.